2022
DOI: 10.3390/ijms23052745
|View full text |Cite
|
Sign up to set email alerts
|

MSCs as Tumor-Specific Vectors for the Delivery of Anticancer Agents—A Potential Therapeutic Strategy in Cancer Diseases: Perspectives for Quinazoline Derivatives

Abstract: Mesenchymal stem cells (MSCs) are considered to be a powerful tool in the treatment of various diseases. Scientists are particularly interested in the possibility of using MSCs in cancer therapy. The research carried out so far has shown that MSCs possess both potential pro-oncogenic and anti-oncogenic properties. It has been confirmed that MSCs can regulate tumor cell growth through a paracrine mechanism, and molecules secreted by MSCs can promote or block a variety of signaling pathways. These findings may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 131 publications
(161 reference statements)
0
6
0
Order By: Relevance
“…Conventional chemotherapy are still limited by some factors including poor pharmacokinetics, accumulation in noncancerous tissues, and toxicity (18). Stem cells are applicable in overcoming these limitations as they can be engineered and used as carriers or vehicles for targeted drug delivery based on the proposition that mesenchymal stem cells (MSCs) undergo chemotaxis toward tumors following the release of chemoattractants like vascular endothelial growth factor (VEGF) (19). Gao et al showed that MSCs are promising in this regard as the stem cells carrying paclitaxel loaded nanoparticles (NPs) were able to deliver their therapeutic pay-load to murine orthotopic glioma cells (20).…”
Section: Stem Cells In Drug Deliverymentioning
confidence: 99%
“…Conventional chemotherapy are still limited by some factors including poor pharmacokinetics, accumulation in noncancerous tissues, and toxicity (18). Stem cells are applicable in overcoming these limitations as they can be engineered and used as carriers or vehicles for targeted drug delivery based on the proposition that mesenchymal stem cells (MSCs) undergo chemotaxis toward tumors following the release of chemoattractants like vascular endothelial growth factor (VEGF) (19). Gao et al showed that MSCs are promising in this regard as the stem cells carrying paclitaxel loaded nanoparticles (NPs) were able to deliver their therapeutic pay-load to murine orthotopic glioma cells (20).…”
Section: Stem Cells In Drug Deliverymentioning
confidence: 99%
“…MSCs have some interesting properties, such as their ability to selectively migrate to local and distant tumoral sites and penetrate the tumor stroma after intravenous injection, as demonstrated in pancreas, melanoma, lung, or breast cancer animal models [86][87][88]. As a vehicle, MSCs may deliver drugs, genes, or other therapeutic agents such as cytokines in various cancers, promoting therapeutic properties, comprising anti-tumor, -proliferative, -inflammatory, -oxidative, or -metastatic effects [240,241]. Numerous studies enumerate the potential benefic effects of MSCs transduced/transfected with viral/non-viral constructs involving the overexpression of therapeutic agents [241][242][243].…”
Section: Mesenchymal Stem Cells As a Therapeutic Tool Against Cancer ...mentioning
confidence: 99%
“…Quinazoline and quinazolinone derivatives have been attracted by biologists and medicinal chemists due to their diverse pharmacological activities [ 19 , 20 ], including anticancer [ [21] , [22] , [23] , [24] ], antitubercular [ [25] , [26] , [27] ], antimalarial [ 28 ], anti-inflammatory [ 29 , 30 ], antimicrobial [ 31 ], anticonvulsant [ 32 ], antihypertensive [ 33 , 34 ], antidiabetic [ 35 ], anti-HIV [ 36 ], antitumor [ [37] , [38] , [39] ], antioxidant [ 40 ], antiviral [ 41 ], kinase inhibitory [ 42 ], sedative-hypnotic, antihistaminic and many other uses [ 43 ]. Quinazoline and its derivatives are promising cancer chemotherapeutic agents for treating solid tumors [ [44] , [45] , [46] , [47] , [48] , [49] , [50] ]. The FDA has approved many quinazoline derivatives for clinical use as cancer treatments.…”
Section: Introductionmentioning
confidence: 99%